Readiness of Local Educational Institution for ISO 9001:2015 Quality Management System Certification: A Comprehensive Analysis - Benjamin Aguenza (Education Policy and Development, 2024)
Business certifications and accreditations are increasingly crucial for organizations, especially in educational institutions, to demonstrate service quality and gain a competitive edge. Quality management systems (QMS) will support these objectives and enhance product and service quality. This study specifically examines the readiness of local educational institution for ISO 9001 Quality Management System certification. It also evaluated the degree of impact among the respondents in terms of compliance with the QMS standard clauses. Additionally, the study identified the challenges faced by local educational institutions in obtaining ISO certification. The research design employed a descriptive approach and a survey questionnaire. Stratified random sampling was used to select a sample of 215 administration and academic personnel. The findings indicated that the assessment level for ISO 9001 is ready. However, among independent variables, leadership is the most important factor in demonstrating a high level of readiness for ISO certification. It emphasizes the importance of adhering to quality management requirements. Furthermore, the assessment differed when respondents were grouped according to their profiles.  In addition, the respondents identified moderate issues related to resistance to change and a lack of proper organizational structure. Therefore, local educational institution must view certification as an ongoing commitment rather than a one-time project. They should establish routine processes to maintain the ISO standard, improve the institution’s image, and raise employees’ awareness of the QMS in their day-to-day operations.